Pengaruh Pemberian Ubi Jalar Ungu terhadap Peningkatan Kadar Haemoglobin Pada Ibu Hamil Trimester III - Elisa Ulfiana; Farida Amalia Yuliandani; Retno Kusuma Dewi; Wilujeng Kartika Ratri (JURNAL KEBIDANAN, 2019)
Maternal Mortality Ratio is an important indicator to determine the degree of public health. causes of maternal death in Indonesia is the most common cause of obstetric direct and indirect maternal deaths due to hemorrhage, eclampsia, complications of abortion, sepsis postpartum, obstructed, including anemia (Depkes RI, 2009). According to data from the Genuk public health center in 2014 the number of hemoglobin levels pregnant women examined 303 people with anemia pregnant women 131 votes (43.23%), while in 2015 the number of hemoglobin levels pregnant women examined 721 people with anemia pregnant women 358 votes (49.65%) so that in the last 2 years an increase in maternal anemia (PHC profile Genuk, 2015).The purpose of this study was to determine the effect of giving sweet potato consumption to hemoglobin levels in third trimester pregnant women. This study uses quasi experiments. The population of this study were TM III pregnant women at the Genuk Health Center, Semarang City using total sampling technique. The results showed that the consumption of sweet potatoes influential to increase the hemoglobin level of pregnant women was indicated by p value 0,000.Expected that midwives can improve health services, especially to overcome anemia in pregnant women by providing health education about the benefits of sweet potatoes as an alternative food ingredient that can increase maternal hemoglobin levels and prevent anemia. Midwives can also encourage pregnant women to consume other food sources  one of them is by consuming sweet potatoes.